2008
DOI: 10.1111/j.1745-3933.2008.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter halo concentrations in the Wilkinson Microwave Anisotropy Probe year 5 cosmology

Abstract: We use a combination of three large N‐body simulations to investigate the dependence of dark matter halo concentrations on halo mass and redshift in the Wilkinson Microwave Anisotropy Probe year 5 (WMAP5) cosmology. The median relation between concentration and mass is adequately described by a power law for halo masses in the range 1011–1015 h−1 M⊙ and redshifts z < 2, regardless of whether the halo density profiles are fitted using Navarro, Frenk & White or Einasto profiles. Compared with recent analyses of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

111
1,409
13
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 939 publications
(1,537 citation statements)
references
References 29 publications
111
1,409
13
4
Order By: Relevance
“…We find that the normalization of the c(M, z) relation is significantly lower than the fiducial Duffy et al (2008) …”
Section: Group Masses and Mass-concentration Relationmentioning
confidence: 85%
See 2 more Smart Citations
“…We find that the normalization of the c(M, z) relation is significantly lower than the fiducial Duffy et al (2008) …”
Section: Group Masses and Mass-concentration Relationmentioning
confidence: 85%
“…We therefore model subhaloes as NFW profiles (equation 8). We assume the c(M, z) relation of Duffy et al (2008); in analogy to equation (10), we set f sub c = 1. To account for the baryonic contribution to the subhalo mass, we include a point mass in the centre with a mass equal to the median stellar mass for each bin (Table 1).…”
Section: Satellite Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous dark-matter-only simulations have shown that the concentration of halos is expected to vary with both redshift and mass on average, and to have an intrinsic scatter of ∼ 20 per cent driven primarily by differences in accretion history (Navarro et al 1997;Bullock et al 2001;Zhao et al 2003Zhao et al , 2009Tasitsiomi et al 2004;Neto et al 2007;Gao et al 2008;Duffy et al 2008;Klypin et al 2011Klypin et al , 2016Ludlow et al 2012Ludlow et al , 2014Prada et al 2012;Dutton & Macciò 2014). Early work suggested a scaling relation similar to c ∝ (1 + z) −1 M −0.13 (Bullock et al 2001).…”
Section: Nfw Concentration-mass Relationmentioning
confidence: 99%
“…In order to explore the parameter space, we will consider models with log Mvir = (14.0, 14.5, 15.0), (z d = 0.3, 0.9, 1.4), and q = (0.75, 0.85, 0.95) and their different combinations. For each (log Mvir, z) combination, we set the concentration cvir using the cvir -Mvir relation of Duffy et al (2008) neglecting its scatter. Note that weak lensing data are presently available for clusters mainly in the mass range (1, 40) × 10 14 M⊙ and redshift 0.2 z 1.4 (Sereno 2015; Groener et al 2015) so that our choice is representative of actual samples.…”
Section: Fiducial Modelmentioning
confidence: 99%